Biological and genomic characteristics of chicken-derived Riemerella anatipestifer in China - Zhang, Yuxia; Wang, Xiaoli; Wang, Yongming; Sun, Jiazhi; Dong, Wenwen; Meng, Kai; Li, Guiming; Yuan, Xiaoyuan (Frontiers in Microbiology, 2025)
IntroductionRiemerella anatipestifer (R. anatipestifer) is a significant bacterial pathogen responsible for serositis, perihepatitis, and encephalitis in waterfowl. Although infections have been extensively reported in ducks, geese, and turkeys, cases in chickens are rarely documented. However, recent evidence indicates that it has emerged as a growing threat to chickens in China in recent years.MethodsIn this study, we collected 120 clinical samples from 30 chicken farms across Shandong and Henan provinces (2023 to 2024) and conducted a comprehensive etiological investigation involving bacterial isolation, antibiotic susceptibility test and genomics analysis. The pathogenic of two R. anatipestifer strains (JN01 and BZ), belonging to serotypes 1 and 10, was evaluated.ResultsOur findings revealed R. anatipestifer as the primary causative agent of the outbreak, with 28 strains successfully isolated. Serotypes 1 and 10 were identified as the predominant epidemic types, while serotypes 7 and 6 appeared sporadically. All isolates exhibited varying degrees of resistance to 15 commonly used antibiotics. Pathogenicity assessment via chicken embryo lethality assay demonstrated that JN01 strain displayed lower virulence than the BZ strain. Experimental infection of specific-pathogen-free (SPF) chickens with a challenge dose of 1 × 108 CFU per chicken successfully reproduced clinical symptoms, with high bacterial loads detected in joint cavities and brains at 10 days post-inoculation. The complete genome of the isolated JN01 was 2,284,590 bp, as determined by third-generation sequencing. Phylogenetic analysis of the whole-genome sequence showed that JN01 is most closely related to strains isolated from ducks within the same clade. Notably, strains from different hosts, including chicken, duck, goose, and tadorna, did not form distinct independent branches but were intermixed throughout the evolutionary tree.DiscussionOur findings demonstrated R. anatipestifer exhibits remarkable host adaptability to chickens. Both the age-dependent susceptibility and clinical manifestations in boilers are essentially consistent with those observed in ducks. The serotypes prevalent in chicken flocks share both similarities and differences with those in duck flocks. Notably, its lethality to chickens is significantly lower than that to ducks. These findings enhance our understanding of the epidemiology and pathogenicity of R. anatipestifer from chicken, providing a scientific foundation for targeted disease prevention and control measures.